2005
DOI: 10.1093/ndt/gfh707
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of renal function in recently admitted critically ill patients with normal serum creatinine

Abstract: In recently admitted critically ill patients with normal serum creatinine, serum creatinine had a low sensitivity for detection of renal dysfunction. Furthermore, the Cockcroft-Gault and MDRD equations were not adequate in assessing renal function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
144
0
14

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(168 citation statements)
references
References 17 publications
10
144
0
14
Order By: Relevance
“…Even if some authors found that these formulas were not optimal for recently admitted critically ill patients (17), the MDRD equation has been found superior to Cockcroft-Gault formulas in renal transplant recipients (30), for predicting aminoglycoside dosing recommendations (5), and in the general population (37).…”
Section: Discussionmentioning
confidence: 99%
“…Even if some authors found that these formulas were not optimal for recently admitted critically ill patients (17), the MDRD equation has been found superior to Cockcroft-Gault formulas in renal transplant recipients (30), for predicting aminoglycoside dosing recommendations (5), and in the general population (37).…”
Section: Discussionmentioning
confidence: 99%
“…However, several limitations exist to the use of CCr in ICU patients. For instance, CCr will often over estimate GFR, especially in patients with AKI, as creatinine is also excreted in the tubules, and establishing steady state conditions is often not possible [30][31][32] .…”
Section: Management Of Persistent Akimentioning
confidence: 99%
“…Hoste et al (18) reported that 25% of patients who were in the ICU and had a normal serum creatinine value (Ͻ1.5 mg/dl) had an estimated GFR Ͻ60 ml/min per 1.73 m 2 as measured with a 1-h creatinine clearance. Of interest, the patients with the low creatinine clearance had a low creatinine generation and were more likely to be ventilated and on vasopressors.…”
Section: Defining Patients At Risk For Acute Renal Injurymentioning
confidence: 99%
“…Some of the problems that are encountered with serum creatinine can be avoided by the use of clearance determinations that are based on timed urinary collections over 1 or 2 h, with blood sampling in the middle to cover potential changes in serum creatinine (18,29,30). This method can be performed accurately only when urine collections occur with an indwelling bladder catheter, but the "GFR" that is based on this measurement still can be inserted into the RIFLE criteria, because a GFR decrease of Ͼ25% meets the criteria for a risk classification.…”
Section: Defining Patients At Risk For Acute Renal Injurymentioning
confidence: 99%